تنسيق زواجل التيار الزائد الاتجاهية في الشبكات المترابطة باستخدام نظام خبير - حجار, عمار (Latakia University Journal -Engineering Sciences Series, 2019)
This paper presents a novel Expert System (ES) for automatic directional inverse overcurrent relays (OCR) coordination in interconnected networks. In the developed ES, the relay setting (determination the pickup current (IPU) and the time dial setting (TDS)) is based on relay setting standards and on the experience of skilled protection engineers. In this paper, the coordination knowledge is represented in a rule-style (IF – THEN – rule structure), and a forward chaining inference engine is used to carry out the coordination process. The facts and the knowledge base (rules) of the developed ES are represented on a personal computer by making use of an expert system shell, CLIPS (C Language Implementation Production System). The developed ES does not depend on the break points determination in performing the coordination process, but it depends only on the iterative search which is conformed to the built in technique of the inference engine. A numerical load flow and fault analysis programs are integrated within the approach. The developed ES is designed to accept different looped networks configurations. The developed ES based protection coordination is tested and validated through different case studies using CLIPS. The results showed that the developed ES is reliable and has a high performance, adequate response time, and flexibility. يقدم هذا البحث نظام خبير جديد لأجل التنسيق الآلي لزواجل التيار الزائد الاتجاهية ذات المميزات العكسية في الشبكات المترابطة. يعتمد تعيير الزواجل في النظام المستحدث (تحديد تيار التعيير و مميزة التشغيل الزمني) على المعايير القياسية لتعيير الزاجل و على خبرة مهندسي الحماية الماهرين. لقد تم في هذا البحث تمثيل الخبرة بالتنسيق بالأسلوب الشرطي (البنية الشرطية - إذا - عندئذ)، وقد استخدمت آلة الاستدلال (الاستقراء و الاستنباط) ذات الاتجاه الأمامي لتنفيذ عملية التنسيق، كما تم تمثيل الحقائق وقاعدة المعرفة (القواعد) للنظام الخبير المستحدث على الحاسوب الشخصي باستخدام بيئة تطوير النظام الخبير المسماة "كليبس" (نظام البناء التنفيذي بلغة سي). إن النظام الخبير المستحدث لا يعتمد على تحديد نقاط القطع في انجاز عملية التنسيق، بل يعتمد فقط على البحث التكراري المتوافق مع التقنية التي تعمل بها آلة الاستدلال. لقد تم إلحاق الطريقة المستحدثة ببرنامجي حساب سريان الحمولة و الأعطال الرقميين، كما أنه تم تصميم النظام الخبير ليقبل أشكال مختلفة من الشبكات المتعددة الحلقات. لقد تم اختبار النظام الخبير المستحدث لتنسيق الحماية و التحقق منه من خلال دراسة حالات مختلفة باستخدام البيئة "كليبس"، حيث أظهرت النتائج أن الطريقة المستحدثة ذات موثوقية، و تملك أداء عالي، و زمن استجابة ملائم، و مرونة.